Insights into Proton Recombination in Ceramic Proton Conducting Electrodes. Issue 4 (22nd April 2021) - Chang, Jian; Lehman, Colin; Vohs, John M.; Gorte, Raymond J.; Vojvodic, Aleksandra; Yang, Kunli; McIntosh, Steven
Abstract : The effect of catalyst addition on H2 evolution from composite electrodes of La0.7 Sr0.3 TiO3 (LST) and BaZr0.1 Ce0.7 Y0.1 Yb0.1 O3− δ (BZCYYb) was studied. Starting with symmetric cells (LST∣∣BZCYYb∣∣LST), Pt was added to one or both electrodes, after which i–V polarization measurements were performed in humidified H2 at 723 and 773 K. The base cells showed very high impedances but these decreased dramatically upon addition of Pt to both electrodes. When Pt was added to only one electrode, the cells performed as diodes, showing that Pt was necessary for H2 dissociation but not for H recombination. The effects of adding Ru, W, Re and Fe were also studied. DFT calculations helped confirm that H recombination on BaZrO3 is expected to be barrierless. The implications of these results for potential application to electrochemical synthesis of ammonia are discussed.